Dzieciństwo w Maroku - Johnsson, Ewa (Studia Edukacyjne, 2021)
This paper is devoted to outlining the child’s situation in the Moroccan socio-cultural reality through the prism of its marginalization. Various factors such as cultural and religious conditions, the family – its structure and economic status, legislative solutions – Family Code Mudawwana, marriage institution, lack of official status, migration, employment, health care and access to education combine to create a map of influences causing specific consequences in the family, in biographies of mothers and finally their children. The purpose of this paper is to produce this map of the problems of today’s Morocco and to make the reader aware of the tragedy and enormity of powerlessness experienced by marginalized, excluded and invisible children. The analysis was based on studies, the latest thematic reports as well as press reports, excerpts of literary texts reflecting the reality of Morocco, or online publications of non-governmental organizations.